2014
DOI: 10.1371/journal.ppat.1004459
|View full text |Cite
|
Sign up to set email alerts
|

Host Cofactors and Pharmacologic Ligands Share an Essential Interface in HIV-1 Capsid That Is Lost upon Disassembly

Abstract: The HIV-1 capsid is involved in all infectious steps from reverse transcription to integration site selection, and is the target of multiple host cell and pharmacologic ligands. However, structural studies have been limited to capsid monomers (CA), and the mechanistic basis for how these ligands influence infection is not well understood. Here we show that a multi-subunit interface formed exclusively within CA hexamers mediates binding to linear epitopes within cellular cofactors NUP153 and CPSF6, and is compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

38
514
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 262 publications
(556 citation statements)
references
References 45 publications
38
514
1
3
Order By: Relevance
“…Paradoxically, PF74 promotes the assembly of recombinant CA in vitro (29), yet the compound destabilizes the viral capsid in native HIV-1 cores (32) and in target cells (32,33). PF74 does not appear to significantly perturb the structure of the CA hexamer, yet the compound binds to the hexamer with higher affinity than to dissociated CA subunits, consistent with the drug target being the assembled capsid (30,31). Partial resistance to PF74 was conferred by 5 mutations in the CA NTD, three of which were in the PF74 binding pocket, and reduced the binding of the compound (29,32).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Paradoxically, PF74 promotes the assembly of recombinant CA in vitro (29), yet the compound destabilizes the viral capsid in native HIV-1 cores (32) and in target cells (32,33). PF74 does not appear to significantly perturb the structure of the CA hexamer, yet the compound binds to the hexamer with higher affinity than to dissociated CA subunits, consistent with the drug target being the assembled capsid (30,31). Partial resistance to PF74 was conferred by 5 mutations in the CA NTD, three of which were in the PF74 binding pocket, and reduced the binding of the compound (29,32).…”
mentioning
confidence: 70%
“…However, loss of binding was not strictly correlated with the degree of resistance, suggesting that coli, as described previously (34,36). The affinities of PF74 for purified CA hexamers were determined by equilibrium dialysis and isothermal titration calorimetry (ITC), as reported previously (30,34). The affinity of Nup153 and CPSF6 peptides for CA hexamers was determined by ITC (30,37).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Full-length CPSF6 is found only in the nucleus of NIH3T3 cells, while the CPSF6 C-terminal truncated protein (CPSF6-358) is localized to the cytosol, suggesting that the RS-like domain is required for its nuclear transport . Price et al (2014) suggested that CPSF6 binds to the N-terminal region of monomeric HIV-1 CA and accommodates NUP153 only when CA exists in its assembled hexameric form, resulting in both being transported into the nucleus by TNPO3 (Price et al 2014). Thus, CPSF6 interacts with intact cores, which are larger than the nuclear pore channel, and impedes nuclear entry.…”
Section: Cleavage and Polyadenylation Specific Factor 6 (Cpsf6)mentioning
confidence: 99%
“…Thus, CPSF6 interacts with intact cores, which are larger than the nuclear pore channel, and impedes nuclear entry. However, CA N74D is insensitive to CPSF6-358 restriction by preventing interaction of CA with CPSF6-358 because N74D requires ligand-specific contact and binds to CPSF6 but not NUP153 (Price et al 2012(Price et al , 2014. The protein interface is conserved both structurally and functionally across diverse lentiviruses, including HIV-2, SIVmac, and FIV.…”
Section: Cleavage and Polyadenylation Specific Factor 6 (Cpsf6)mentioning
confidence: 99%